(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Aims and Objectives: The study was conducted to evaluate the efficacy, safety, complications and the results of Litholopaxy for bladder stones Study Type; Case Study Place and Duration of study; Obaid Noor Hospital Mianwali from july 01, 2010 to june 30,2013. Material & Methods: This was a prospective case study conducted at Obaid Noor Hospital Mianwali in Urology Department. The patients were selected by simple random means. The procedure was based on the principles of endoscopic removal of bladder stones using mauremayer stone punch. The patients were evaluated by detailed history, clinical examination, ultrasonography, radiography, routine urine examination and urine cultur and sensitivity test. We studied the results of 70 patients with bladder stones treated by cystolitholapaxy. The other concomitant pathologies were BPH, Strictur Urethra, and Bladder diverticuli which were treated by TURP and Optical Urethrotomy along with cystolitholapaxy..We also studied the comlications and limitations of the procedure. Results: All the patients were treated successfully with fewer complications. The overall success rate was 95.17%.There were no bladder perforation or excessive bleeding in any case requiring exploration. The complications included mild hematuria in 19(27.14%),pyrexia in 10(14.28%) and Suprapubic pain in 07(10%)patients. Conclusion: The study shows that litholopaxy has reduced post operative complications and morbidity rate, shorter operative time and reduced period of hospitalization. Therefore it is safe, convenient and cost affective method for treatment of bladder stones.